Causes and Consequences of Internal Migration in Bhaktapur District, Nepal - Bohara, Pradeep Kumar (Educational Journal, 2023)
This field-based study, titled "Causes and Consequences of Internal Migration in Madhyapurthimi municipality ward 5, Bhaktapur," aimed to assess the demographic profile of in-migrants, understand the reasons for internal migration in the study area, and explore the outcomes of internal migration. The research relied on both primary and secondary data sources, with information gathered from 110 households through structured and semi-structured interviews. Upon collecting and thoroughly reviewing the data, the study revealed several key findings. It was observed that a significant proportion of in-migrants were students and job seekers, primarily falling within the age group of 20 years, which constitutes the economically active population. The analysis of respondents' income sources in their places of origin indicated that 50% relied on agriculture, 26.4% on business, 19.1% on services, and 4.5% on labor for their income. Regarding the demographic composition of the surveyed population, out of a total of 427 individuals across the 110 selected households, 49.18% were male, and 50.82% were female. The predominant religious affiliations were Hinduism (84.3%), followed by Buddhism (7.5%), Christianity (4.7%), and Kirat (3.7%), with the lowest percentage belonging to the Kirat faith. Education-wise, 56.52% of the population was found to have received formal education. The study highlighted that the primary drivers of in-migration were a lack of access to quality education and healthcare services, limited employment opportunities, and challenges in meeting the household's basic needs.